The Improvement Understand through Development of Digital’s Teaching Materials Oriented on Interactive Lecture Demonstrations Model on Particle Dinamic’s Material - Novitasari, Novitasari; Sari, Elisa Mayang; Pratiwi, Indah Riezky; Pebriano, Gagah (Kasuari: Physics Education Journal (KPEJ), 2024)
Understanding is a basic middle level thinking skill based on the revised Bloom's taxonomy. One learning model that is student-centered is Interactive Lecture Demonstration (ILDs). Surveys prove that particle dynamics is one of the physics topics that is difficult for students to understand. As a result, students cannot construct their own understanding. The development of ILDs model-oriented digital teaching materials is a solution. The subjects focused on students in class XI Science in two classes which were used as experiment and control. Development research applies four stages, including definition, design, development and dissemination. The aim of this development is to improve the ability to understand. So for dissemination, mixed research methods are applied with a sequential explanatory strategy. This strategy was chosen because research is dominated by quantitative research. Subjects were given two instruments, namely a comprehension ability test to obtain an overview of comprehension abilities that can be strengthened through the implementation of digital teaching materials and an attitude scale sheet to see students' perspectives regarding the implementation of digital teaching materials. The results obtained by the characteristics of teaching materials contain a series of stages of the ILDs model and can improve understanding abilities.